Pengaruh Gerakan Perempuan Terhadap Partisipasi Politik Perempuan di Indonesia dan Amerika Serikat - Raissa Ardianti (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2016)
The dominance of men in a system of government has been common in various countries. In Indonesia, there have been sexist perceptions of women circulating, even though it is known that there have been a series of laws that protect women's involvement in politics. It is regrettable that the Indonesian people have not yet considered the low representation of women in government as a problem. In comparison, the representation of women in the United States is also not better than Indonesia. Interestingly, in the United States it is known that there are many movements initiated by women. The question arises to what extent a system of government, feminist culture, and the legal umbrella in both Indonesia and the United States influence women's participation in the government system. This article further elaborates on the low escalation of women's issues in politics through a comparison between Indonesia and the United States.